Electronic Cigarette Prevalence and Patterns of Use in Adults with a History of Cardiovascular Disease in the United States. Issue 9 (13 September 0207) - Stokes, Andrew; Collins, Jason M.; Berry, Kaitlyn M.; Reynolds, Lindsay M.; Fetterman, Jessica L.; Rodriguez, Carlos J.; Siegel, Michael B.; Benjamin, Emelia J.
Abstract : Background: Characterizing electronic cigarette (e‐cigarette) use patterns is important for guiding tobacco regulatory policy and projecting the future burden of tobacco‐related diseases. Few studies have examined patterns of e‐cigarette use in individuals with cardiovascular disease (CVD). Methods and Results: We examined e‐cigarette use in adults aged 18 to 89 years with a history of CVD, using data from the 2014 National Health Interview Survey. We investigated associations between ever and current e‐cigarette use and smoking with multivariable logistic regression. In a secondary analysis, we modeled the association between e‐cigarette use and a quit attempt over the past year. Former smokers with CVD who quit smoking within the past year showed 1.85 (95% confidence interval, 1.03, 3.33) times the odds of having ever used e‐cigarettes as compared with those who reported being "some days" current smokers. Current smokers who attempted to quit smoking within the past year showed significantly increased odds of ever having used e‐cigarettes (odds ratio, 1.70; 95% confidence interval, 1.25, 2.30) and currently using e‐cigarettes (odds ratio, 1.97; 95% confidence interval, 1.32, 2.95) as compared with smokers who had not attempted to quit over the past year. Conclusions: Individuals with CVD who recently quit smoking or reported a recent quit attempt were significantly more likely to use e‐cigarettes than current smokers and those who did not report a quit attempt. Our findings may indicate that this population is using e‐cigarettes as an aid to smoking cessation. Characterizing emerging e‐cigarette use behaviors in adults with CVD may help to inform outreach activities aimed at this high‐risk population.